Positioning and Surveying Requirements for Exploration and Exploitation of Ocean Wealth - Pathak, M. C.; Kotnala, K. L.; Prabaharan, N.; Ganesan, P. (The International Hydrographic Review, 2015)
Deep sea mining, such as is now being planned to be carried out in the Indian Ocean, requires an accurate positioning system for navigation and for the control of the equipment. Short range systems using electromagnetic principles cover only a limited area while the longer range systems which can be used for offshore, deep ocean work although covering large areas, have limited accuracy. This paper reviews the requirements for position fixing systems for deep ocean mining and the ways to reach the best solution at the most reasonable cost.